Production and Characterization of PLA/HA/GO Nanocomposite Scaffold - Oktay, Busra; Ahlatcıoğlu Özerol, Esma; Sahin, Ali; Gunduz, Oguzhan; Ustundag, Cem Bulent (Wiley, 2022)
Abstract Polylactic acid (PLA) composite nanofibers combined with hydroxyapatite (HA) and graphene oxide (GO) nanoparticles were produced by electrospinning to create excellent biodegradable and durable scaffolds to be used in tissue engineering. The properties of the pure PLA, PLA/HA, PLA/GO, and PLA/HA/GO nanocomposite scaffolds were analyzed in chemical, morphological, mechanical, and biocompatibility. Morphology and composition were investigated by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), respectively. To predict the cytocompatibility of these scaffolds, HFF‐1 cells were cultured and the respective cell adhesion and proliferation were investigated by fluorescence microscopy, SEM, and MTT assay. FTIR results showed the successful synthesis of HA and GO nanoparticles. SEM images showed that the PLA/HA/GO scaffold is ideal for cell attachment and proliferation in tissue regeneration. Mechanical test results showed that the tensile strength and elastic modulus of PLA nanofibers could be increased by adding 0,8 wt % HA and 0,4 wt % GO. The PLA/HA/GO scaffold exhibited the highest tensile strength of other scaffolds. MTT assay revealed that the PLA/HA/GO scaffold showed significantly high biocompatibility with 105 % cell viability. Therefore, PLA/HA/GO scaffold with 0,8 wt %HA and 0,4 wt %GO possessing high tensile strength as well as good cell proliferation is an excellent and versatile biomaterial for tissue engineering applications.
Keywords: Graphene; Alkoloidler; Strategies; Kimya (çeşitli); Temel Bilimler (SCI); Fabrication; Kimya, multidisipliner; Biochemistry; Kimya; Hydroxyapatite (HA); Scaffold; Chemistry; Biyokimya; Alcaloides; Polylactic acid (PLA); Biomaterials; Composite; Temel Bilimler; General Chemistry; MECHANICAL-PROPERTIES; Genel Kimya; Chemistry; Fizik Bilimleri; Chemistry (miscellaneous); Tissue; Chemistry, multidisciplinary; Natural Sciences (SCI); Physical Sciences; Bone Tissue Engineering; Natural Sciences; Graphene Oxide; BONE